Catecholaminergic polymorphic ventricular tachycardia: a rare cause of recurrent syncope - Azevedo, Ana Isabel (Oxf Med Case Reports, 2015)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmia characterized by adrenergically induced polymorphic or bidirectional ventricular tachycardia (VT). Although a rare disease, its recognition is important because of its high mortality rate when left untreated. We report an index case of a 32-year-old woman who presented with recurrent syncope. The diagnosis was confirmed by exercise-induced polymorphic ventricular premature beats and episodes of non-sustained VT, in the absence of structural heart abnormalities. She remained event free with beta-blocker therapy. CPVT is a potentially life-threatening disease and should be considered in the case of recurrent syncope, in young individuals. Diagnosis is based on clinical history and exercise testing, which is the gold standard. Therapy is mandatory in all diagnosed individuals. Exercise testing in first-degree relatives is recommended, even in the case of a mutation-negative index patient.